2009
DOI: 10.1038/nchembio.246
|View full text |Cite
|
Sign up to set email alerts
|

A synergistic small-molecule combination directly eradicates diverse prion strain structures

Abstract: Safely eradicating prions, amyloids and preamyloid oligomers may ameliorate several fatal neurodegenerative disorders. Yet, whether small-molecule drugs can directly antagonize the entire spectrum of distinct amyloid structures or ‘strains’ that underlie distinct disease states is unclear. Here, we investigated this issue using the yeast prion protein Sup35. We have established how epigallocatechin-3-gallate (EGCG) blocks synthetic Sup35 prionogenesis, eliminates preformed Sup35 prions, and disrupts inter- and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
240
0
1

Year Published

2010
2010
2013
2013

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 93 publications
(248 citation statements)
references
References 50 publications
6
240
0
1
Order By: Relevance
“…3), further indicated that EGCG directly bound and stabilised TTR tetramer in vitro, and induced TTR oligomerisation in cells 34 . The pharmaceutical mechanism of EGCG curing of yeast prions [PSI] could be via stabilisation of the native prion domain Sup35 as well 35 .…”
Section: Attenuation Of Tdp-43 Degradation By Egcgmentioning
confidence: 99%
“…3), further indicated that EGCG directly bound and stabilised TTR tetramer in vitro, and induced TTR oligomerisation in cells 34 . The pharmaceutical mechanism of EGCG curing of yeast prions [PSI] could be via stabilisation of the native prion domain Sup35 as well 35 .…”
Section: Attenuation Of Tdp-43 Degradation By Egcgmentioning
confidence: 99%
“…Alzheimer | Parkinson | catechine | misfolding | oligomer P revious studies have shown that the polyphenol (-)-epi-gallocatechine gallate (EGCG), found in large amounts in green tea, has antiamyloidogenic properties and modulates the misfolding of disease proteins and prions (1)(2)(3)(4)(5). EGCG directly binds to unfolded polypeptide chains and inhibits β-sheet formation, an early event in the amyloid formation cascade (6).…”
mentioning
confidence: 99%
“…The general mechanism of EGCG has now been confirmed in various misfolded protein systems [81,95,96] and the yeast prion Sup35 [86]. However, mechanistic details seem to depend on the stability of the protein aggregates that are formed with the aid of EGCG.…”
Section: Mechanism Of Egcg Interventionmentioning
confidence: 96%
“…Since then, it has been shown that EGCG binds directly to a large number of proteins that are involved in protein misfolding diseases and that EGCG inhibits their fibrillization. Examples include αS [81,82], Aβ [36,82], transthyretin [83], lysozyme [84], the prion protein PrP [85], and the yeast prion Sup35 [86].…”
Section: Mechanism Of Egcg Interventionmentioning
confidence: 99%
See 1 more Smart Citation